Carbon Emissions Due to Construction of Building Using Cement-Stabilized Compressed Earth Bricks and Comparison with Conventional Fired Earth Bricks - Dulal, Prakash; Giri, Rabindra Raj (Kathford Journal of Engineering and Management, 2023)
Carbon emission from human activities including civil engineering constructions has been a major global environmental issue. The emissions due to the use of conventional fired earth bricks (CFEB) in the construction industry are significantly larger, and a large number of researches have been devoted to developing viable alternatives to the uses of CFEB in the construction industry to achieve a low-carbon society. This research investigated carbon emissions due to the use of cement-stabilized compressed earth blocks (CSCEB) in place of CFEB in the construction of a community building in Bidur Municipality, Nuwakot, using the standard tools and methods by the Intergovernmental Panel on Climate Change (IPCC) guidelines. Also, the Bilan Carbone tool was used. Then the emission results of the two cases (CSCEB and CFEB) were compared from different perspectives. Among the considered major emission sectors, the construction materials sector contributed the highest carbon emissions in both bricks. Results indicate that CSCEB requires lower quantities of cement, sand, and aggregates compared to CFEB. Major construction materials contribute significantly to carbon emissions, with CSCEB showing a 1.7 times lower impact than CFEB. The total carbon emissions for CSCEB and CFEB were 160.97 and 206.42 Tons of CO2 equivalents in this study. That is, the total carbon emission from CFEB construction was about 1.3 times of the CSCEB. Furthermore, the direct emissions in both cases were almost the same, while the 1.4 times larger emission in the case of CFEB was the sole contribution of indirect emissions. The results of this study once again demonstrated that CSCEB can be an alternative to CFEB in the construction industry to achieve the objective of a low-carbon society.